Knowledge, Awareness and Behaviors of Somalian Female University Students regarding Cervical Cancer, HPV and the HPV Vaccine: A Cross-Sectional Study - Şeyma Zehra Altunkurek; Samira Hassan Mohamed (IMR Press, 2024)
Background: Awareness and knowledge of cervical cancer and human papillomavirus (HPV) are consistently poor in low-resource settings. In addition, there is insufficient evidence about young people's knowledge and understanding of cervical cancer, risk factors, screening and HPV vaccination in these countries. This study was conducted to determine the knowledge, attitudes and behaviors of students studying at a university in Somalia regarding cervical cancer and how to prevent it. Methods: This cross-sectional study was conducted among students of the Faculty of Health Sciences at a private university in Mogadishu, Somalia, between January and March 2021. The sample of study consisted of a total of 220 female students. The data of the study were collected using a questionnaire consisting of 32 questions evaluating the knowledge and attitudes of the students regarding cervical cancer, HPV and the HPV vaccine. Results: In the study, 59.1% of the participants stated that they had previously heard of cervical cancer, 69.1% did not know that it was fatal, 49.1% stated that it was preventable, 48.2% did not know the causes of cervical cancer, and 2.7% had a family history of cervical cancer. In addition, it was determined that 75.9% of the participants did not know that HPV caused cervical cancer. When the knowledge of the participants about HPV and the HPV vaccine was examined, it was determined that 55% of them had not previously heard of HPV. When asked about how HPV is transmitted they stated that this occurred through kissing (73.2%), sexual intercourse (58.2%) and using items owned by individuals infected with HPV (41.8%). None of the participants had received the HPV vaccine. Of these, 72.3% stated that they had not been vaccinated because they did not know about the vaccine. According to 40.9% of the participants, both boys and girls should be vaccinated; however, 63.6% stated that they did not know at what age individuals should receive a vaccine. In addition, 71.4% of participants said they did not know that the HPV vaccine protects against HPV-related sexually transmitted diseases. There was a statistically significant relationship only between the participants' financial status and the awareness variable (p < 0.05). It was concluded that the awareness of those participants whose economic situation was good was statistically high. Conclusions: This was our first study on the subject in Somalia and it revealed that the level of knowledge of female university students studying in the field of health sciences regarding cervical cancer, the HPV vaccine and prevention methods were insufficient, as were the vaccination rates. In future research, the reasons for these inadequacies should be revealed through more comprehensive studies.